Current Status of Research on Kidney and Psychiatric Disorders (Dementia as an Example) - Wang, Xia; Li, Ke; Liu, Yanni (Journal of Contemporary Medical Practice, 2024)
Dementia is a relatively severe and persistent cognitive disorder. It is characterized by slowly progressive intellectual decline, accompanied by varying degrees of changes in behavioral patterns and interpersonal relationships, but there is no impairment of consciousness. It is a group of clinical syndromes, the etiology of dementia is many, most of the dementia in modern medical research is often due to brain damage or brain lesions, and in the Chinese medicine theory system of the cognition of this syndrome and the five organs of the five organs of the official - the kidney has a close connection, the mechanism of the trick can be explained through the following points of view: the kidney is the master of the bone, the bone generates the marrow, the marrow is filled with the brain (brain is the sea of the medulla oblongata), the brain is the house of the spirit of the first, and the whole body is closely related through the meridians, has the ability to regulate the whole body, has the ability to regulate the whole body, has the ability to regulate the whole body. The whole body is closely associated with the physiological functions of the body and preside over the thinking and consciousness activities, regulate emotions, dominate and control the behavior of the integrated role of the brain for the essence, gas, God, three infusion of the Qi Heng of the internal organs, to the essence for the body, the gods for the use of the three through the mutual sustenance, the transformation of each other so that the body through the qi to achieve normal physiological functions, thus showing the body's flexibility and agility of the process of activities, meticulous and subtle thinking and consciousness, and rich expression of emotions, very good. As well as rich emotional expression, it is a good reflection of the role of "Kikyo" and the mechanism of coordination and unity within the human body. In view of the dementia symptoms caused by various diseases in modern medicine, this paper mainly expounds on the dialectical relationship between various parts of the organism in the Chinese medicine theory system in terms of etiology, pathogenesis and clinical diagnosis and treatment.